PENGARUH PELATIHAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PERIKANAN KABUPATEN SELUMA - Dwi Kartika, Anggun; Ilhami, Mardhiyah Dwi (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2024)
This research aims to determine "The influence of training and work motivation on employee performance at the Seluma Regency Fisheries Service", either partially or simultaneously. The type of research used is quantitative research. The population in this study were 50 employees at the Seluma City sub-district office in the Seluma Regency Fisheries Service, using the side total technique, which means the entire population was used as the research sample. The collection technique uses questionnaire data that has been tested for validity and reliability. The data analysis technique used to answer the hypothesis is Multiple Regression. The results of this research show that: (1) The research results show a positive influence of training variables on employee performance. Based on the results of the partial test ( T test ), the T_count was 3.321 and the regression coefficient was 0.189 with a significance of 0.002. (2) The research results show a positive influence of the Work Motivation variable on Employee Performance. Based on the results of the partial test ( T test ), the T_count is 2,773 and the regression coefficient is 0.144 with a significance of 0.000. (3) The results of simultaneous testing or jointly obtained that the Training and Work Motivation variables have a positive effect on employee performance. This is proven by the test results obtained by an F_count value of 5,567, with significance (0.007 < 0.050). Keywords: Training, Work Motivation, Employee Performance